Physician Prescribing and Referral Patterns in Children with Cerebral Visual Impairment. Issue 9 (September 2021) - Rice, Melissa L.; Sandoval, Monica A.; Castleberry, Katherine M.; Schwartz, Terry L.
Abstract : SIGNIFICANCE: Cerebral visual impairment (CVI) is the leading cause of visual impairment in the developed world. Providing children with CVI with the appropriate treatment ensures the best possible visual outcome and potentially improves quality of life. PURPOSE: The purpose of this study was to determine physician prescribing and visual rehabilitation referral patterns in children with CVI. METHODS: A retrospective chart review was completed on children with CVI examined at Cincinnati Children's Hospital Medical Center from January 1, 2008, to March 1, 2018. Significant refractive error warranting correction was determined using the American Academy of Ophthalmology Preferred Guidelines and the American Association for Pediatric Ophthalmology and Strabismus Vision Screening Committee Guidelines. The CVI Range was used as a surrogate to categorize CVI severity. RESULTS: A total of 194 children were included. Sixty-eight (35%) had refractive error warranting correction and were prescribed glasses (group RC), 99 (51%) did not have refractive error warranting correction and were not prescribed glasses (group NRNC), 20 (10%) had refractive error warranting correction but were not prescribed glasses (group RNC), and 7 (4%) did not have refractive error warranting correction but were prescribed glasses (group NRC). There was greater than one-line Snellen equivalent difference between group RC (20/156) and group RNC (20/221). There was greater than six-line Snellen equivalent difference between group NRNC (20/149) and group NRC (20/35). Mean CVI Range score 2 values for each group were 5.9, 4.6, 4.8, and 7.1. CONCLUSIONS: Children with less severe CVI were less likely to have significant refractive error but given glasses. Despite significant refractive error, children with more severe CVI were not prescribed glasses. Children with very low visual function were not prescribed glasses as frequently, possibly limiting their visual rehabilitation. Providers should ensure that all children with CVI are correctly prescribed glasses to provide the best possible visual outcome.